Immunogenicity of yeast-derived hepatitis B vaccine from two different producers. - Dahl-Hansen, E. (Cambridge University Press, 1990)
The immunogenicity and reactogenicity of two preparations of yeast-derived hepatitis B vaccines were compared in healthy adult populations. The two groups were vaccinated in parallel, but they were not matched for age and sex. All subjects seroconverted, and 9 months after the first vaccine dose, all had anti HBs titres of at least 10 IU/l. The anti-HBs titres were higher in the group of subjects given 20 micrograms vaccine antigen made by Smith Kline & RIT (GMT 2943 at 9 months) compared to those who received 10 micrograms of vaccine made by Merck, Sharp & Dohme (GMT 729 at 9 months). Adverse effects were recorded in 32.0 and 44.7% of the participants, but these were limited to minor local and general reactions. In the present study both preparations were safe and efficient.